How to draw mecha robots : and battle fantasy figures - Bergin, Mark , 1961- (How to draw, 2007)
Part of "The How To Draw" series, this work teaches you how to draw a variety of robots and machines, and combine them to make your own sci-fi and fantasy scenes. It includes background detail on each robot.